NECESIDAD DE REFORMAR EL ART.- 57 DE LA LEY ORGANICA REFORMATORIA A LA LEY DE MINERIA, SOBRE LA AFECTACION SOCIAL QUE PRODUCE LA DESTRUCCION, DEMOLICION, INUTILIZACION O NEUTRALIZACION DE MAQUINARIA EQUIPOS, INSUMOS Y VEHICULOS UTILIZADOS EN ACTIVIDADES ILEGALES DE EXPLOTACION MINERA - PULLAGUARI DIAZ, MAYRA LORENA (2015)
The research is the subject of this work that I put to the consideration of the National University of Loja and the general public arising from the need for an analysis of the issue entitled "Art.- NEED FOR REFORM 57 ORGANIC LAW REFORM MINING LAW ON THE SOCIAL INVOLVEMENT RESULTING IN DESTRUCTION, DEMOLITION, CANCELLATION OR NEUTRALIZATION MACHINERY EQUIPMENT, SUPPLIES AND VEHICLES USED IN ILLEGAL MINING" social problems arising from its application, as based the implementation of this article has been destroyed many machines seized in illegal mining; thus highlighting that the main consequence has been indirectly and significantly affecting the whole country, since they are denied citizens the right to use these material resources in works of multiple benefits for them; that is why it is necessary to reform the mining legislation on the subject pointed according to the social reality that encompasses this issue. I made the focus of that problem from the point of social, economic and legal terms, analyzing it in its national and international context, based on the study of comparative law, from which I can propose recommendations and solutions to this problem as well as well as develop a draft legal reform that can somehow help to confront this social setback. From the above comes the importance and timeliness of this issue that allowed me to approach it and analyze it from all its contexts, in order to propose viable solutions legal order. 5 Art. 57 of the Organic Law Amending the Mining Act states that should take effect destruction, demolition, deactivation or neutralization of heavy machinery used in illegal mining activities, however not taken into account the great need for the country to use such machinery in public infrastructure, agricultural production or to implement equipment machinery municipal GAD country among others; it is noteworthy that the Constitution of the Republic guarantees as a fundamental right of people Good Living or Sumak Kawsay which defines it as the satisfaction of the basic needs of the population, ie provide it with everything needed to enable them a simple and modest but dignified and happy with quality of life and well-being for its people life.